Reusable Respiratory and Skin Protective Devices Will Help Russian NBC Protection Troops to Avoid Pathogenic Biological Agents - Valerii V. Vasilyev; Sergei N. Solovykh; Nikita V. Danyakin.; Pavel V. Gorbachev (Вестник войск РХБ защиты, 2024)
Highlights. As a novel coronavirus infection spreads around the world, it is crucial to provide Russian NBC Protection Troops with respiratory and skin protective devices that will help them to avoid pathogenic biological agents.Relevance. A common protective set is the only authorized equipment that is able to protect skin of military men from pathogenic biological agents. When military men wear this suit during disinfection of special vehicles, edifices, buildings and plots of land, personnel decontamination in case of biological contamination area is found, it sometimes immobilizes them excessively and they feel completely exhausted. Thus, it is crucial to develop a new more efficient respiratory and skin protective set for the Russian NBC Protection Troops that will help them to avoid pathogenic biological agents.Purpose of the study is to make proposals for the design and materials that are to be used in manufacturing of the set of respiratory and skin protective devices. This set will further be sent to Russian NBC Protection Troops and will help them to avoid pathogenic biological agents.Materials and methods. The materials selection and design features choice have been justified by the analysis of academic sources and patents. The authors have also conducted a questionnaire survey for experts. The results of this survey have been considered in the study. The materials for a future set have been chosen based on the results of the experimental studies of more than 100 of material samples. These samples have been provided by the industrial enterprises of the region. During the studies, a gravimetric method has been employed. Some design features of the set have been implemented pursuant to expert opinions, expressed in the questionnaires.Discussion. With the help of the authorities of the Kostroma region, the authors of this paper have analyzed more than 100 fabrics that are to be used in manufacturing of respiratory and skin protective devices. They also have evaluated the impact that detergent formulae exert on the material properties.Conclusions. The conducted tests have helped to make recommendations, suggestions as well as elaborate certain engineering solutions. Considering all that the enterprises started a large-scale production of efficient respiratory and skin protective devices for medical staff in Kostroma and other regions of the Russian Federation. Design features of garment with respiratory and skin protective devices have served as a pattern for a promising protective set for Russian NBC Protection Troops that will help them to avoid pathogenic biological agents.